Investigação do desenvolvimento de tolerância cruzada aos óleos essenciais de Origanum vulgare L. e Rosmarinus officinalis L. e perda da culturabilidade em células de Listeria monocytogenes - Barbosa, Isabella de Medeiros (2019)
Listeria monocytogenes is the etiological agent of a gastrointestinal disease known as listeriosis, and has been linked to several outbreaks involving ready-to-eat products, mainly animal origin products. Its importance in food is related to its ability to withstand adverse conditions found in food processing environments and in food matrices. Therefore, the aim of this study was to evaluate whether pre-exposure (24, 48 and 72 h) to sublethal concentrations (1/2 MIC, 1/4 MIC and 1/8 MIC) of organic acids (acetic acid and lactic acid) and salts (sodium chloride and potassium chloride) could induce the development of cross-tolerance to Origanum vulgare L. (OVEO) and Rosmarinus officinalis L. (ROEO) essential oils (EO) in three strains of L. monocytogenes. It was further investigated whether exposure to OVEO (2.5 and 5 µL/mL) and ROEO (5 and 10 µL/mL) in PBS and meat broth could develop in L. monocytogenes a “viable but non culturable state (VBNC). The minimum inhibitory concentration (MIC) of organic acids, salts and EO was determined by the broth microdilution method. The induction of tolerance was assessed by MIC modulation and survival curves assay. Culturability loss/recovery was evaluated by the viable cell counts method. The effect of stressing agents and EO tested on different physiological parameters (membrane integrity and potential and respiratory, enzymatic and efflux activities) were monitored by flow cytometry (FC). The results obtained in the induction of tolerance assays showed that preexposure to organic acids and salts did not induce the development of cross-tolerance to OVEO, however, induced increased tolerance to OERO. In the MIC modulation assay, MIC of OVEO decreased up to 10 times the initial MIC value, while the MIC of OERO increased up to 4.8 times. In the survival curves assay, OVEO decreased the counts of cells pre-exposed and non pre-exposed to stressing agents, while ROEO decreased only non pre-exposed cell counts. The culturability loss/recovery assay showed that L. monocytogenes cells treated in PBS lost their culturability after 60 min of exposure to OVEO (2.5 and 5 µL/mL) and ROEO (10 µL/mL) and after 180 min to ROEO (5 µL / mL); when treated in meat broth, the loss of culturability occurred after 180 min for both OVEO (2.5 and 5 µL/mL) and ROEO (5 and 10 µL/mL). Cells that were exposed to OVEO were unable to restore their culturability after recovery treatment in PBS added 0.2% glucose. However, cells exposed to ROEO in PBS (5 µL/mL) and meat broth (5 and 10 µL/mL) restored their culturability after 24 hours of recovery treatment. Results from FC analysis showed that all functions monitored in L. monocytogenes cells pre-exposed to AA or NaCl and treated with OVEO or ROEO were affected, although in different intensities. Cells that lost culturability after exposure to OVEO or ROEO showed that all monitored functions were damaged. However, after recovery treatment, for cells that did not recover culturability, an improvement was observed in most of the evaluated physiological parameters, indicating cell viability. These data indicate that exposure to stressing conditions imposed by organic acids or salts may result in the development of cross-tolerance to ROEO but not to OVEO, however, stressing conditions caused by both EO may induce a VBNC state in L. monocytogenes which, in turn, can restore its ability to multiply under favorable conditions, making it a hazard to consumers’ health.